SAT0223 The Diagnostic Utility of Fluorescence Optical Imaging in Evaluating Synovitis of the Hands and Wrists. (10th June 2014) - Győri, N.; Kisten, Y.; Rezaei, H.; Karlsson, A.; Romanus, C.; af Klint, E.; van Vollenhoven, R.
Abstract : Background: The timely identification of synovial inflammation is critical for early diagnosis & treatment of rheumatoid arthritis & other inflammatory arthritides. Fluorescence Optical Imaging (FOI, "Rheumascan"), a novel imaging modality, uses an intravenous fluorescence dye, that enables imaging of the hands & wrists with increased optical intensities in areas of high perfusion &/or capillary leakage. Objectives: To determine the sensitivity & specificity of FOI as a diagnostic tool in determining "active" synovitis as compared to the US & clinical findings. Methods: A total of 748 joints of both hands & wrists, including 3 wrist joints, 5 MCPs, 5 PIPs, & 4 DIPs in 22 patients (15 female, 7 male) with an age average of 44yrs old, with inflammatory arthritis (RA: 9; JIA, psoriatic arthritis, SLE, polyarthritis & other diagnoses, 1-2 each) were examined clinically, by US & FOI. Only swollen & tender joints were regarded as clinically inflamed. Positive colour Doppler US signals with synovial thickening/fluid were considered as "active" synovitis. FOI was scored visually. Comparisons were done using kappa statistics, and the diagnostic utility (sensitivity & specificity) of FOI was tested. Results: 72 out of 748 joints (10%) were considered inflamed by clinical examination, 144 (19%) by US, and 129 (17%) by FOI. Of the clinically inflamed joints, 49 (68%) were identified as "actively" inflamed by ultrasound, and 37 out of 72 (51%) of these joints were inflamed by FOI. Out of 676 joints that were negative by clinical examination, 581 (86%) were negative by ultrasound and 575 (95%) by FOI. The agreement between clinical examination & US was fair (kappa 0.37±0.05) and somewhat stronger than the agreement between clinical examination & FOI (kappa 0.28±0.05). Out of 144 joints that were "actively" inflamed by US, 100 (69%) showed inflammation by FOI, while out of 604 non-inflamed joints by US, 575 (95%) were non-inflamed by FOI. The agreement between US and FOI was good (kappa 0.67±0.04). Out of 49 joints that were inflamed both by clinical examination & by US, 27 (55%) were inflamed by FOI. Conclusions: The sensitivity of FOI for inflammation in individual joints of the hands & wrists were 51-76% depending on what "gold standard" was used to define inflammation. The specificity of FOI was 95% (575/604), suggesting that it has lower sensitivity but similar specificity compared to US. These findings, together with good agreement between US & FOI, suggest that the latter may be used as a complementary diagnostic tool in clinical practice, in particular when US is not available, in order to identify synovitis earlier and with greater confidence. Acknowledgements: To the patients & all involved in this study in one way or the other. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2484